2019
DOI: 10.33594/000000189
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor Improves Remodeling, Reduces Apoptosis, Inflammation and Fibrosis and Increases the Number of Progenitor Stem Cells After Myocardial Infarction in a Rat Model of Ischemia Reperfusion

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…In addition, ticagrelor improved EF 4 weeks after ischemia/reperfusion by attenuating fibrosis and decreasing the mRNA level of collagen-III, but clopidogrel did not. Moreover, ticagrelor decreased the levels of interleukin-1β, proinflammatory tumor necrosis factor-α, and interleukin-18, while increasing the levels of anti-inflammatory 15-epi-lipoxin-A4 [ 85 ], in agreement with other research [ 86 ]. To date, there has been no large randomized, double-blind, and multicenter research to investigate whether ticagrelor can improve myocardial remodeling after myocardial infarction.…”
Section: Reducing Ischemia-reperfusion Injury and Improving Cardiac F...supporting
confidence: 89%
“…In addition, ticagrelor improved EF 4 weeks after ischemia/reperfusion by attenuating fibrosis and decreasing the mRNA level of collagen-III, but clopidogrel did not. Moreover, ticagrelor decreased the levels of interleukin-1β, proinflammatory tumor necrosis factor-α, and interleukin-18, while increasing the levels of anti-inflammatory 15-epi-lipoxin-A4 [ 85 ], in agreement with other research [ 86 ]. To date, there has been no large randomized, double-blind, and multicenter research to investigate whether ticagrelor can improve myocardial remodeling after myocardial infarction.…”
Section: Reducing Ischemia-reperfusion Injury and Improving Cardiac F...supporting
confidence: 89%
“…According to the study by Birnbaum et al 29 , ticagrelor, possibly by inducing a local increase in extracellular adenosine levels, may augment reparative mechanisms that attenuate adverse remodeling and fibrosis, and it may increase cell proliferation and stem cell recruitment. Based on these data, it may provide an alternative approach to cardioprotection and stem cell therapy, as evidenced by improved cardiac function 29 .…”
Section: Discussionmentioning
confidence: 99%
“…These drugs bind to P2Y 12 , the adenosine diphosphate (ADP) receptor of platelets, and prevent blood coagulation ( 93 ). A recent study has shown that ticagrelor may have a positive effect in ameliorating pulmonary fibrosis in rats ( 96 ). Likewise, prasugrel may have positive effects on relieving hepatic fibrosis ( 90 ).…”
Section: Anticoagulants In Organ Fibrosismentioning
confidence: 99%
“…Likewise, prasugrel may have positive effects on relieving hepatic fibrosis ( 90 ). However, further research is necessary for these drugs to be used in human clinical trials as it is unclear, whether the effects in animal studies would be translatable to patients is unclear ( 96 ).…”
Section: Anticoagulants In Organ Fibrosismentioning
confidence: 99%